To strength human rights, change the OAS (not the Commission) - Canton, Santiago A. (2013)
Evaluates the impact of the Inter-American System for Human Rights (IASHR) on the member states of the OAS. Takes a look at the reforms needed to strengthen the body. Argues that substantive reform of the OAS would not only resolve most of the challenges of this body, but it would also help to redefine the role of an organisation that, with the exception of its work on human rights, has become outdated in a fast changing region that is turning its back on this once relevant regional organisation.